The Tomárâho conception of the sky - Sequera, G. (2011)
The small community of the Tomárâho, an ethnic group culturally derived from the Zamucos, have become known in the South American and world anthropological scenario in recent times. This group, far from the banks of the Paraguay river, remained concealed from organized modern societies for many years. Like any other groups of people in close contact with nature, the Tomárâho developed a profound and rich world-view which parallels other more widely researched aboriginal cultures as well as showing distinctive features of their own. This is also apparent in their imagery of the sky and of the characters that are closely connected with the celestial sphere. This paper is based on the lengthy anthropological studies of G. Sequera. We have recently undertaken a project to carry out a detailed analysis of the different astronomical elements present in the imagined sky of the Tomárâho and other Chamacoco ethnic groups. We will briefly review some aspects of this aboriginal culture: places where they live, regions of influence in the past, their linguistic family, their living habits and how the advancement of civilization affected their culture and survival. We will later mention the fieldwork carried out for decades and some of the existing studies and publications. We will also make a brief description of the methodology of this work and special anthropological practices. Last but not least, we will focus on the Tomárâho conception of the sky and describe the research work we have been doing in recent times. © International Astronomical Union 2011.